Effects of auxins and boron on rooting of kiwi stem cuttings (Actinidia chinensis Pl cv Matua) - Ono, E. O.; Rodrigues, J. D.; dePinho, S. Z. (Fundacion Romulo Raggio, 1995)
This work studies the effects of some synthetical auxins and boron in the rooting of stem cuttings of kiwi (Actinidia chinensis Planch cv Matua). The stems used had two nodes and two leaves cut in half. The auxin effect was observed through seven different treatments: T1 (H2O); T2 (NAA 300 ppm); T3 (IBA 300 ppm); T4 (NAA 300 ppm + B); T5 (IBA 300 ppm + B); T6 (NAA 0,5%-talc) and T7 (IBA 0,5%-talc), applied to the bases of stem cuttings. After these treatments, the cuttings were placed in suitable rooting dishes, with pure vermiculite in misty nebulization chamber for 120 days until collection day. The evaluation of auxin and boric acid effects were made based on the following observations: 1. The percentage of rooted stem cuttings; 2. reducing sugar and total sugar analyses; and 3. tryptophan analyses. The effects of such treatments were observed in the four seasons. The results showed that winter is best for rooting. Application of IBA talc 0,5% to the cuttings bases increased rooting.
Keywords: Actinidia chinensis; IBA; NAA; boron; rooting; cuttings